Case of allergic contact dermatitis due to 1, 3‐butylene glycol. Issue 9 (September 2014) - Aizawa, Atsuko; Ito, Akiko; Masui, Yukiko; Ito, Masaaki
Abstract 1, 3‐Butylene glycol (1, 3‐BG) is widely used in cosmetics, including low‐irritant skin care products and topical medicaments, as an excellent and low‐irritation humectant. We report a case of allergic contact dermatitis caused by 1, 3‐BG. A 28‐year‐old woman suffered from an itchy erythematous eruption on her face. By 2 days of closed patch testing, her own cosmetics and many of the hypo‐irritant skin care products showed positive results. A second patch testing showed positive reaction to 1, 3‐BG (1% and 5%). 1, 3‐BG was a common component in most of the products that had elicited a positive reaction in the first patch testing. Although allergic contact dermatitis due to 1, 3‐BG is not so common, we have to consider 1, 3‐BG as a possible contact allergen in the patients presenting with allergic contact dermatitis due to various cosmetics.